2007
DOI: 10.1249/01.mss.0000274464.50186.ed
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Consumer Grade Bioelectrical Impedance Analysis Devices Compared to Air Displacement Plethysmography

Abstract: Int J Exerc Sci 4(3) : [176][177][178][179][180][181][182][183][184] 2011. The purpose of this study was to examine the accuracy of percent body fat estimates from seven different bioelectrical impedance analysis (BIA) models and a seven-site skin fold formula (SKF) compared with air displacement plethysmography (ADP) in females. Eighty-two female volunteers ranging from 19-67 years (31.96 ± 1.39) enrolled in this study. Body composition was assessed by seven site skin folds (SKF), ADP, Tetrapolar BIA (TBIA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Evidence of adherence to this practice is noted in research utilizing the traditional BIA method with electrodes in the tetrapolar wrist-to-ankle configuration. 6,8 Other studies have modified the recommendation and reported that their participants were supine between 5 and 10 min prior to assessment. 9,10 No literature was found substantiating the recommendation that it takes the full 10 min to stabilize the water compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of adherence to this practice is noted in research utilizing the traditional BIA method with electrodes in the tetrapolar wrist-to-ankle configuration. 6,8 Other studies have modified the recommendation and reported that their participants were supine between 5 and 10 min prior to assessment. 9,10 No literature was found substantiating the recommendation that it takes the full 10 min to stabilize the water compartments.…”
Section: Introductionmentioning
confidence: 99%
“…For the current study, our findings indicated that the Omron 306 reported higher %BF than did the InBody 720 in a majority of the participants. Peterson et al (2011) found that the multifrequency octopolar measures used for this study had similar %BF to ADP, and therefore, we can assume that the InBody 720 is a better measure of body fat than the Omron 306. It could be expected that the prevalence of the youth at risk for metabolic syndrome determined in another study of this supplement (Laurson, Welk, Marton, Kaj, & Csányi, this issue) could be overestimated; however, metabolic syndrome is a cluster of several risk factors, and therefore, the impact of the Omron 306 was likely minimized.…”
Section: S63mentioning
confidence: 52%
“…An Omron HBF-500 has been tested on college students with favorable results in male students (Pribyl, Smith, & Grimes, 2011) and female students (Peterson, Repovich, & Parascand, 2011) using the ADP (e.g., BOD POD) as the criterion measure. In the latter study, its accuracy was shown to be superior (less residual) to the Omron 306, which was also included in the comparison study.…”
Section: S63mentioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) actually came to light in the mid1980s with commercial availability of impedance analyzers [126,127]. At first, BIA use took a great extent in nutritional assessment [124], but in time its use also expanded into the area of health monitoring among the general population [126,128]. Although there are varying types and methods of measurement, today the fundamental principles of BIA remain the same.…”
Section: Bioimpedancementioning
confidence: 99%